(untitled) (Research, Society and Development, 2021)
Objective: to describe the experience in the teaching-learning process of the mental health discipline, remotely, in the training of nursing technicians. Methodology: this is a descriptive study, of the experience report type, about the teaching-learning process of the mental health discipline, taught remotely during the Covid-19 pandemic to a group of students from a Nursing Technician course. Results and Discussion: this manuscript is based on the report and reflection of experiences during the mental health curriculum component, in remote format, carried out in the first half of 2021. The experience allowed the elaboration of two categories: the first focuses on theoretical discussions the basic contents of mental health among students and teachers, and the second highlights the academy-service integration, from the perspective of the role and performance of different health professionals in psychosocial care services. Final considerations: the report and reflection of experiences lived during the mental health course revealed possibilities to teach theoretical contents, as well as to carry out internship activities in an off-site manner.